A Facile Solvent Strategy Enables Morphology Controllable Perovskite Films for CsPbBr3 Perovskite Solar Cells. Issue 6 (24th January 2023) - Wang, Shiyu; Liu, Jiale; Chen, Mingyue; Lu, Yu; Zhao, Yue; Qi, Pengcheng; Ran, Hongbing; Mei, Anyi; Tang, Yiwen; Han, Hongwei; Hu, Yue
Abstract : The CsPbBr3 perovskite solar cells (PSCs) display extensive potential due to their good thermal and humidity stability, but the presence of heterogeneous phases severely limits the further improvement of device performance. Phase‐pure monoclinic CsPbBr3 can be stabilized by using the printable mesoscopic device structure. However, it is challenging to obtain high‐quality perovskite crystals in such confined space. Herein, a solvent strategy is used for improving the perovskite crystallization in the printable mesoscopic structure. By using N‐methylformamide as the precursor solvent, the PbBr2 exhibits a more uniform and controllable distribution, which benefits the CsPbBr3 crystallization. As a result, the CsPbBr3 inside the pores showed obvious orientation at (100) lattice plane and (110) crystal plane. The efficiency of modified PSCs increases from 7.53% to 8.32%. Based on the device with effective area of 1 cm 2, the PSCs obtain a power conversion efficiency of 5.62%. In addition, PSCs show no obvious attenuation after 1000 h of maximum power point tracking, displaying the excellent illumination stability. Abstract : Herein, a solvent strategy by using N‐methylformamide as the precursor solvent of PbBr2 is used for improving the perovskite crystallization in the printable mesoscopic structure. The efficiency of perovskite solar cells (PSCs) increases from 7.53% to 8.32%. In addition, PSCs show no obvious attenuation after 1000 h of maximum power point tracking, displaying excellent illumination stability.